Benefits of Health and Wellness Education in the Adult Population in México, 2006 - Juan Manuel Hernández Vázquez (Universidad Autónoma de Baja California, 2013)
This paper presents advances in understanding the influence of Mexican education on the perceptions of the adult population regarding their health. The analysis forms part of the oecd conceptual model for understanding the connections between education and social-but not economic-outcomes. Data from the 2006 National Survey on Health and Nutrition is employed to build a logistic model. The study confirmed the idea that people tend to feel healthier as their educational level rises, regardless of their economic condition, ethnicity, age, gender or whether they reside in a rural or urban area. The findings also showed that education is the single most positive influence on the perception of feeling healthy, more so even than economic situation.